The Moral Personality of the Russian Revolutionary - Wojtowicz, Kamil (Hybris, 2025)
From the second half of the 19th century in Tsarist Russia, due to turbulent politics and social changes, revolutionary groups (Narodnik, socialist, and anarchist) developed rapidly. To fully capture this period in the history of Russian revolutionary thought, it seems crucial to understand the ethos of a revolutionary and the moral personality that should define them. Therefore, the following article presents the personality of the Russian revolutionary. First, the concept of moral personality is briefly presented, followed by a presentation of the “Catechism of the Revolutionary” by Sergei Nechayev as a work containing premises as to the nature of the moral personality of the (anarchist) revolutionary. What follows is a reconstruction of the moral personality of a (socialist) revolutionary based on Russian revolutionary literature. The article ends with a summary underlying the conclusions from the analysis of the texts, indicating the character of the moral personality of the Russian revolutionary.